2008
DOI: 10.1007/s10734-008-9158-9
|View full text |Cite
|
Sign up to set email alerts
|

Reflection on teaching and epistemological structure: reflective and critically reflective processes in ‘pure/soft’ and ‘pure/hard’ fields

Abstract: We empirically explored whether academics from pure/soft and pure/hard fields engage in reflective practice on teaching differently and, if so, whether these differences could be partially explained by the epistemological structure of their discipline. Interview data from academics in pure/hard (N = 30) and pure/soft fields (N = 10) were deductively analyzed according to different types and domains of reflection as well as the nature of learning underlying these reflections. The greatest differences between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 32 publications
(64 reference statements)
3
48
0
2
Order By: Relevance
“…While the scheme has been used for research in countries as varied as Korea (Shin, 2011), Australia (Smith & Miller, 2005) and Canada (Kreber & Castleden, 2009), there appears to have been little previous attempt to see if the same classification scheme applies in these other countries, let alone see if the link between disciplines and the classification scheme matches up. This study provides strong support for suggesting that the pure/applied and hard/soft classifications do retain validity in the UK context and that the match between disciplines and classification is very close.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the scheme has been used for research in countries as varied as Korea (Shin, 2011), Australia (Smith & Miller, 2005) and Canada (Kreber & Castleden, 2009), there appears to have been little previous attempt to see if the same classification scheme applies in these other countries, let alone see if the link between disciplines and the classification scheme matches up. This study provides strong support for suggesting that the pure/applied and hard/soft classifications do retain validity in the UK context and that the match between disciplines and classification is very close.…”
Section: Discussionmentioning
confidence: 99%
“…While Jones (2011) places it alongside the model from Smart, Feldman, and Ethington (2000), Biglan's scheme is cited more than five times as often, even accounting for its earlier publication. It has received widespread use in many analyses within higher education including teachers' reflective practice (Kreber & Castleden, 2009); the relationship between class size and grades (Johnson, 2010) and even the proportion of positive result reported in hypothesis testing papers (Fanelli, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Rotidi (2016) also found that critical reflection of assumptions (Mezirow, 1991), which is the highest level of critical reflection and the most important precondition for the transformation of a teaching perspective, was not common in any of the three knowledge domains of academics' knowledge (Kreber, 2004;2005;Kreber and Castleden, 2009). Greek academics, mostly coming from Soft fields, provided evidence of premise reflection, more frequently observed within the domains of Pedagogical and Instructional Knowledge.…”
Section: Clues For Teaching Patterns In Greek Universitiesmentioning
confidence: 99%
“…Content reflection is described by Mezirow (1991) as a process in which we "are not attending to the grounds or justification for our beliefs but are simply using our beliefs to make an interpretation" (p107). Kreber and Castleden (2009) dimensions on an equal footing with cognitive and rational components" (pp. 66-67).…”
Section: Behavioural Outcome Patternsmentioning
confidence: 99%